Studies in Buddhist philosophy - Siderits, Mark (Oxford University Press, 2016)
This volume brings together 19 of Mark Siderits's most important essays on Buddhist philosophy. Together they cover a variety of topics, from metaphysics, logic, philosophy of language, epistemology, and ethics, to the specific discussions of the interaction between Buddhist and classical Indian philosophy